Two new species of the genus Tautoneura Anufriev from Karst area in Southwest China (Hemiptera: Cicadellidae: Typhlocybinae) - Tan, Wei-Wen; Pu, Tian-Yi; Song, Yue-Hua (Zootaxa, 2022)
Two new species of the leafhopper genus Tautoneura Anufriev from Karst areas in Southwest China are described and illustrated, Tautoneura aureomarginalis sp. nov. and Tautoneura lageniformis sp. nov. A key to distinguish the Chinese species of the genus is given.